SEARCHING FOR AN APPROPRIATE EFL CURRICULUM DESIGN FOR THE INDONESIAN PLURALISTIC SOCIETY - Suwarsih Madya (TEFLIN Journal: A publication on the teaching and learning of English, 2007)
The context of the teaching of English in Indonesia is indeed unique, leading to differences in the ease with which children have access to education. Those with great difficulty in accessing education have been and will be left behind by those without any or with little difficulty. Technology will certainly help in easing those in remote areas. The limited financial capacity, however, has made it impossible to have equity in educational access; the equity problem remains unsolved. Under such a complex environment, a more appropriate curriculum design should be sought. So far the same national standard has to be achieved by children. This paper explores possibilities of having a multi-standards English curriculum design aimed at providing every child to learn according to their abilities and rates of learning. A three-level standard curriculum is then proposed: the instrumental standard for highly advantaged children, the functional standard for those who are fairly advantaged, and the appreciative standard for those who are disadvantaged.